CHARACTERIZATION OF MYCOPLASMA GALLISEPTICUM ISOLATED FROM COMMERCIAL POULTRY FLOCKS - M. A. Gondal; M. Rabbani; K. Muhammad; T. Yaqub; M. E. Babar; A. A. Sheikh; A. Ahmad; M. Z. Shabbir; M. I. Khan (Journal of Animal and Plant Sciences, 2015)
Chronic Respiratory Disease (CRD) is caused by Mycoplasmas gallisepticum (MG) and is prevailing in layer, broiler and breeder poultry flocks. The infected birds showed sneezing, rales, coughing and exudates from nostrils and eyes. Mycoplasma species were recovered 27.3% overall, 39.3 per cent of the tracheal swabs, 15.9 per cent of tracheal tissues, 27.4 per cent of lung tissues and 25 per cent of air sacs. Polymerase chain reaction confirmed the nucleic acid of the MG from tracheal swabs (68.18%), tracheal tissues (42.47%), lung tissues (31.85%) and air sacs (50%) using universal and MG specific primer. Higher percentage of MG confirmation through PCR is due to detection of nucleic acid of MG from medicated birds. It is concluded that culture method was laborious and time consuming and failed to detect mycoplasma species from medicated birds and is less sensitive than that of PCR. PCR is rapid, sensitive and accurate method for diagnosis of MG from suspected cases.
Keywords: Mycoplasma gallisepticum; CRD; PCR; Frey’s broth